Historical Analysis of the Phillips Curve in the Turkish Economy (Third Sector Social Economic Review, 2026)
The aim of this study is to analyze the relationship between inflation and unemployment in Turkey over the 1930–2024 period on a periodic basis within the framework of the Phillips Curve and to evaluate the validity of this relationship in a historical context. The study adopts both an empirical and a historical–social perspective, examining not only the statistical interaction between macroeconomic variables but also the broader implications of this relationship for economic stability, income distribution, and policy preferences. The existing literature on Turkey presents conflicting findings regarding the validity of the Phillips Curve: while some studies report a partially supported inverse relationship in the short run, the evidence suggests that this relationship becomes inconsistent over longer periods characterized by economic crises and structural imbalances.Using an extensive dataset spanning nearly a century, the study analyzes the Turkish economy across distinct macroeconomic regimes namely the statism period, import substitution industrialization, the liberalization process, and the globalization era and evaluates the validity of the Phillips Curve for each period through both graphical and statistical methods. As the primary empirical approach, the relationship between the annual inflation rate (measured by the CPI percentage change) and the unemployment rate is tested using simple regression analysis for each sub-period. The direction and strength of the relationship are interpreted based on slope coefficients, their signs, and R² values. In addition, periodic scatter plots are employed to provide visual insights, and the empirical findings are systematically linked to major historical economic events and policy shifts in Turkey.The aim of this study is to analyze the relationship between inflation and unemployment in Turkey over the 1930–2024 period on a periodic basis within the framework of the Phillips Curve and to evaluate the validity of this relationship in a historical context. The study adopts both an empirical and a historical–social perspective, examining not only the statistical interaction between macroeconomic variables but also the broader implications of this relationship for economic stability, income distribution, and policy preferences. The existing literature on Turkey presents conflicting findings regarding the validity of the Phillips Curve: while some studies report a partially supported inverse relationship in the short run, the evidence suggests that this relationship becomes inconsistent over longer periods characterized by economic crises and structural imbalances.Using an extensive dataset spanning nearly a century, the study analyzes the Turkish economy across distinct macroeconomic regimes namely the statism period, import substitution industrialization, the liberalization process, and the globalization era and evaluates the validity of the Phillips Curve for each period through both graphical and statistical methods. As the primary empirical approach, the relationship between the annual inflation rate (measured by the CPI percentage change) and the unemployment rate is tested using simple regression analysis for each sub-period. The direction and strength of the relationship are interpreted based on slope coefficients, their signs, and R² values. In addition, periodic scatter plots are employed to provide visual insights, and the empirical findings are systematically linked to major historical economic events and policy shifts in Turkey.
Keywords: Phillips Curve; Inflation; Unemployment; Turkish Economy; History of Finance